Distribution and composition of Dragonfly and Damselfly species (Odonata) of the upper Rio das Velhas, Ouro Preto, Minas Gerais State, Brazil - Ávila Júnior, Walter Francisco de (2020)
This paper describes the composition and distribution of Anisoptera and Zygoptera (Odonata) species of the upper Rio das Velhas in the municipality of Ouro Preto, Minas Gerais State, Brazil. A total of 727 specimens of 40 species were collected near water bodies over a period of 23 months between 2015 and 2017. The families with greatest species richness were Libellulidae (13 species), Coenagrionidae (12 species) and Heteragrionidae and Aeshnidae (4 species each). Notable among the species collected were Perilestes fragilis Hagen in Selys, 1862, inhabiting well-preserved forests, Minagrion waltheri Santos, 1965, pertaining a endemic genus of Brazil and the recently described Heteragrion cauei Ávila-Júnior et al., 2017, and three species recorded for the first time for the state: Elasmothemis alcebiadesi (Santos, 1945); Erythrodiplax melanica Borror, 1942 and Erythrodiplax acantha Borror, 1942, the latter is considered Critically Endangered (CR) by the International Union for Conservation of Nature's (IUCN) Red List.